Centenary event photos of the Club of St Anthony of Deussua - Mumbai Archive Project (Jio Institute, 2024)
The Club of St. Anthony of Deussua is more than 140 years old. It was established in 1880. In 1980, the club celebrated its centenary year under the ownership and management of the Catholic community in Deussua. Some photographs of the centenary event are displayed in the reception hall.